Autoestima y la conducta alimentaria en adolescentes de la ciudadela “El Fortín” de la ciudad de Guayaquil - Hinojoza Taco, María Alicia (2024)
Eating behaviors worldwide are complex mental health diseases that are related to other types of factors such as low self-esteem, body image and beauty stereotypes; that affect adolescents and young women; these are some of the factors that have led to eating behaviors being the third common chronic disease among young people, reaching an incidence of 5%. For the World Health Organization, AC is among the groups of mental illnesses as a priority for children and adolescents with the health risks that these behaviors imply. In the present study the objective is to analyze the eating behaviors that affect the self-esteem of adolescents in the citadel "El Fortín" of the city of Guayaquil of passages 11, 12, 13,14, 15; whose population is 150 adolescents, through a simple random sampling formula, data were obtained from 72 adolescents ranging from 12 to 19 years old, who participated in the two established phases; As a first instance, we had to perform the Rosenberg self-esteem test that evaluates the level of self-esteem and a second questionnaire (EAT-26) that assesses possible eating behaviors. According to the results obtained, the population has low and average self-esteem; through which (EAT-26) had 35% of possible cases of eating behavior. Finally, it was determined that there is a possible relationship between eating behaviors and self-esteem.